Raising public awareness of aphasia in southern Ontario, Canada: A survey. (April 2015) - Patterson, Ruth; Robert, Amélie; Berry, Richard; Cain, Mallory; Iqbal, Maryam; Code, Chris; Rochon, Elizabeth; Leonard, Carol
Abstract Purpose: Despite the relatively high prevalence of aphasia, research indicates that, world-wide, public awareness of aphasia is lacking. Of the surveys that have been conducted internationally, none has studied the Canadian public's awareness of aphasia. The purpose of the present survey was to assess public awareness and basic knowledge of aphasia of individuals in southern Ontario, Canada. Method: Using the same questionnaire that has been used in other countries, face-to-face surveys were conducted in public places (e.g. parks) at various locations in southern Ontario. Respondents were asked questions pertaining to their awareness and knowledge of aphasia. The number of surveys retained for analysis was 831. In addition to an evaluation of public awareness and knowledge of aphasia, the potential influences of age, gender, and occupation were analysed. For those who had heard of aphasia, questions were asked to determine how or where they had heard of aphasia. Result: Consistent with the literature, overall public awareness and basic knowledge of aphasia in southern Ontario was found to be limited. The factors of age, gender and occupation were found to influence the results. Conclusion: This investigation supports the need for better promotion of aphasia awareness to the public in southern Ontario and, by extension, in Canada.